2012
DOI: 10.1002/pen.23289
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel poly(butylene succinate)‐based copolyesters designed as potential candidates for soft tissue engineering

Abstract: Poly(butylene succinate/diglycolate) copolymers by reactive blending were subjected to molecular and solidstate characterization to study the effects of transesterification reactions. 13 C-nuclear magnetic resonance analysis evidenced the formation of block copolymers. Thermal measurements showed that all the samples were semicrystalline, with a soft amorphous phase and a rigid crystal phase. Wide-angle x-ray diffraction measurements indicated that the copolymers are characterized by cocrystallization. The mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 17 publications
(17 reference statements)
3
42
0
Order By: Relevance
“…As it can be seen from the data reported in Table 2, the glass transition temperature and &C p values were not influenced by the presence of nanofillers and the results here presented are in good agreement with those previously obtained for neat polymers [24]. During the second heating scan, DSC traces of neat polymers showed multiple melting peaks, due to melt-recrystallization processes [26]. With the addition of increasing amounts of SWCNTs, this phenomenon progressively disappeared, and single melting endotherms could be observed.…”
Section: Thermal and Structural Characterizationsupporting
confidence: 80%
“…As it can be seen from the data reported in Table 2, the glass transition temperature and &C p values were not influenced by the presence of nanofillers and the results here presented are in good agreement with those previously obtained for neat polymers [24]. During the second heating scan, DSC traces of neat polymers showed multiple melting peaks, due to melt-recrystallization processes [26]. With the addition of increasing amounts of SWCNTs, this phenomenon progressively disappeared, and single melting endotherms could be observed.…”
Section: Thermal and Structural Characterizationsupporting
confidence: 80%
“…Gigli et al . reported that PBDG had a T d of 330 °C, and PBS had a T d of 305 °C . Therefore, the thermal stability of the synthesized PBDG sample in this work was comparable to that of the sample reported by Gigli et al .…”
Section: Resultssupporting
confidence: 84%
“…In recent years, the synthesis and physical properties of poly(diethylene glycol succinate) (PDEGS), poly(triethylene dodecanoate) (PTED), and poly(butylene diglycolate) (PBDG) containing ether linkages have been reported in literature . It should be emphasized that all of these polyesters are highly hydrophilic and flexible.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations